Volatile organic compounds: plant natural defense mechanisms against herbivorous arthropods and an opportunity for plant breeding of cotton - Villamar-Torres, Ronald (2018)
Plants’ natural defense mechanisms against herbivorous arthropods include the emission of volatile organic compounds (VOC). Nowadays field observations about plant-insect interactions are better understood thanks to the increasingly scientific investigations over recent decades. There are now more precise data about molecules, action modes and physiological and genetic bases of these plant defense mechanisms. VOC present an important potential for crop protection and pesticide use reduction. In the present review, we focus on the latest research advances about plant protection provided by VOC, considering experimental methods of volatile analysis and the involved genes toward genetic improvement of natural defense in the future varieties, particularly for Upland cotton Gossypium hirsutum.